COMPOSITE BASED ON AGRICULTURAL WASTE FOR USE AS LINING POULTRY HOUSES - Cravo, J. C. M.; Sartori, D. de L.; Balieiro, J. C. de C.; Fiorelli, J. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The lining is an alternative to smoothen the flow of heat to the interior of the poultry housing. However, the main insulating materials are toxic when burned. From this perspective, this study investigated the thermal properties and durability of the effect on the mechanical properties of a composite based agricultural waste for use as lining in poultry houses. Peanut shell and coconut fiber were used (50:50) and 15% bi-component polyurethane resin to castor oil-based. The specific heat, thermal diffusivity and thermal lag were measured and compared with other insulating materials. The effect of durability performance was evaluated by rupture modulus and elastic modulus. The thermal results reported that the composite has potential for application as thermal insulation, while the evaluation of the durability revealed the need to incorporate a coating to ensure consistency of mechanical properties of the composite.